MTHFR Gene Polymorphism and Diabetic Retinopathy - Maeda, Makiko; Fujio, Yasushi; Azuma, Junichi (Current Diabetes Reviews, 2006)
Diabetic retinopathy (DR) is the leading cause of catastrophic loss of vision. Each year, DR darkens the lives of 12,000 to 24,000 diabetic patients in the United States, and more than 4,000 patients in Japan. Clinically, hyperglycemia induces proliferative changes in DR synergistically with other risk factors for vascular diseases. Methyl- enetetrahydrofolate reductase (MTHFR) is an enzyme involved in remethylation of homocysteine to methionine. A polymorphic mutation (C677T) in the MTHFR gene leads to impaired enzyme activity, resulting in hyper- homocysteinemia as an independent risk factor for macroangiopathy. Recently, more and more attention has been paid to the involvement of hyperhomocysteinemia in the progression of DR, a serious microangiopathic complication of diabetes. Clinical studies have demonstrated that MTHFR gene polymorphism can contribute to the progression of DR, especially in the patients with blood glucose poorly controlled. Furthermore, accumulating evidence suggests that homocysteine activates vascular inflammation through inflammatory cytokines, including VEGF. These data imply that the decrease in plasma homocysteine could prevent the development and progression of DR. We also propose the possibility of personalized medicine for diabetes mellitus based on a better understanding of MTHFR gene polymorphism and its ramifications, which might cast new light on diabetic retinopathy.
Keywords: MTHFR